2021
DOI: 10.1186/s40635-021-00384-w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation preserves diaphragm mitochondrial function in a rat sepsis model

Abstract: Background To describe the effect of mechanical ventilation on diaphragm mitochondrial oxygen consumption, ATP production, reactive oxygen species (ROS) generation, and cytochrome c oxidase activity and content, and their relationship to diaphragm strength in an experimental model of sepsis. Methods A cecal ligation and puncture (CLP) protocol was performed in 12 rats while 12 controls underwent sham operation. Half of the rats in each group were p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The Extensor digitorum longus (EDL), fast-twitch muscle, ex vivo -specific force decreases 1 week and 1 month in septic induced by cecal slurry compared with control mice ( Owen et al, 2019 ). Moreover, the ex vivo diaphragm function was reduced 6 and 24 h after sepsis induction ( Zolfaghari et al, 2015 ; Eyenga et al, 2021 ). This model resamples severe acute sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Extensor digitorum longus (EDL), fast-twitch muscle, ex vivo -specific force decreases 1 week and 1 month in septic induced by cecal slurry compared with control mice ( Owen et al, 2019 ). Moreover, the ex vivo diaphragm function was reduced 6 and 24 h after sepsis induction ( Zolfaghari et al, 2015 ; Eyenga et al, 2021 ). This model resamples severe acute sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it did not present a significant change in the SOD protein level ( Talarmin et al, 2017 ). Another group demonstrated that acute sepsis increased H 2 O 2 production in the diaphragm ( Eyenga et al, 2021 ). Reduction in Sod expression observed herein can be a consequence of the decrease in Pgc1 α observed ( Figures 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown, in an experimental model of sepsis, that early initiation of mechanical ventilation restores mitochondrial function in the diaphragm. In this study, not only did mechanical ventilation preserve the cytochrome c oxidase content and activity in the diaphragms of septic rats, but it also maintained the efficiency of oxidative phosphorylation (ATP:O) and lowered mitochondrial ROS production by Complex III [79]. In addition to these simple resuscitation measures, interfering with the inflammatory system [80] or cell signaling pathways [56] could improve the function of cytochrome c oxidase.…”
Section: Therapeutic Implicationsmentioning
confidence: 70%
“…Moreover, the authors did not quantify the content of the cytochrome c oxidase subunit, so it cannot be excluded that the increase in oxygen consumption reflected increased oxygen reduction, but without efficient proton pumping [52]. Two recent studies have examined the effect of common symptomatic treatments for sepsis on the function of cytochrome c oxidase in the liver [78] and diaphragm in a rodent model of sepsis [79]. Yang et al [78] have shown that fluid resuscitation improves the function of cytochrome c oxidase; however, the mechanism remains unclear.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Given the dense packing of mitochondria in skeletal muscles due to their high metabolic demand, a significant amount of reactive oxygen species (ROS) is produced in muscles after damage, a factor considered crucial for muscle functions. It has been established that ROS, primarily originating from mitochondria in the diaphragm, contributes to mitochondrial oxidative stress (MOS), playing a key role in promoting protein degradation and exacerbating VIDD [25,26]. Additionally, oxidative stress is known to activate a feedback loop with ROS, promoting autophagy, thereby creating a cycle of increased ROS generation and elevated autophagy levels [27].…”
Section: Discussionmentioning
confidence: 99%